Correlation of Apparent Diffusion Coefficient with Neuropsychological Testing in Temporal Lobe Epilepsy - Lui, Yvonne W.; Nusbaum, Annette O.; Barr, William B.; Johnson, Glyn; Babb, James S.; Orbach, Darren; Kim, Alice; Laliotis, Georgia; Devinsky, Orrin (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Patients with nonlesional temporal lobe epilepsy have long been known to have abnormalities of memory. Recently, these patients have been shown to have increased diffusivity in the hippocampus. We hypothesized that in these patients, a negative correlation would exist between diffusivity measures of the mesial temporal lobe and performance on neuropsychological tests.METHODS: Twenty presurgical patients with temporal lobe epilepsy and 20 age- and sex-matched healthy controls underwent MR imaging of the brain. Apparent diffusion coefficient region of interest measures were taken in both hippocampi and parahippocampal gyri by 2 independent observers. Mean whole brain diffusivity was calculated. All patients completed neuropsychological testing. Electroencephalogram and pathology results were collected. Patients and controls were compared with respect to each apparent diffusion coefficient measure. In patients, apparent diffusion coefficients ipsilateral and contralateral to the seizure focus were compared. Associations were assessed between diffusivity measures and neuropsychological scores.RESULTS: Eleven patients had right-sided seizure foci and 9 had left-sided seizure foci. Patients demonstrated higher apparent diffusion coefficient values than controls over the whole brain, in the hippocampi, and in the parahippocampal gyri (P < .05). Patients demonstrated higher apparent diffusion coefficient within the ipsilateral hippocampus (1.19 ± 0.22 × 10−3 s/mm2) and parahippocampal gyrus (1.02 ± 0.12 × 10−3 s/mm2) compared with the contralateral side (1.02 ± 0.16 × 10−3 s/mm2 and 0.96 ± 0.09 × 10−3 s/mm2, respectively) (P < .05). Negative correlations were seen between hippocampal apparent diffusion coefficients and multiple memory tests (P < .05).CONCLUSION: Quantitative diffusion measurements in the hippocampus correlate with memory dysfunction in patients with temporal lobe epilepsy.